Causes of fatigue in elite football: A survey of elite football stakeholders - Bahdur, K. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction In sport, burnout contributes to decreased performance, increased risk of injury, sports dropout and decreased mental and physical health. Mental fatigue (MF) and physical fatigue (PF) are precursors to burnout. Most research focuses on the physical load experienced during training and competition. In the modern game, elite football stakeholders are exposed to on and off-field stressors which may cause fatigue. The purpose of this study was to subjectively identify factors that contribute to fatigue and identify the type of fatigue that manifests because of exposure to these causes.